2018
DOI: 10.5194/hess-2018-317
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of univariate and multivariate bias correction on hydrological impact projections in alpine catchments

Abstract: Abstract. Alpine catchments show a high sensitivity to climate variation as they include the elevation range of the snow line. Therefore, the correct representation of climate variables and their interdependence is crucial when describing or predicting hydrological processes. When using climate model simulations in hydrological impact studies, forcing 10 meteorological data are usually downscaled and bias corrected, most often by univariate approaches such as quantile mapping of individual variables. However, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Meyer et al. (2019) used MBCn to investigate the bias‐correction effect in hydrological impact studies. They showed that MBCn‐corrected GCM‐RCM data caused more precipitation to fall as snow.…”
Section: Resultsmentioning
confidence: 99%
“…Meyer et al. (2019) used MBCn to investigate the bias‐correction effect in hydrological impact studies. They showed that MBCn‐corrected GCM‐RCM data caused more precipitation to fall as snow.…”
Section: Resultsmentioning
confidence: 99%
“…The N-dimension multivariate bias correction (MBCn) by Cannon (2018) was selected in this study to correct biases of hourly precipitation and temperature. MBCn was chosen because it is arguably the most advanced quantile-based multivariate bias correction method available (Meyer et al, 2019;Chen et al, 2018).…”
Section: Bias Correctionmentioning
confidence: 99%
“…The interdependence of key climate variables, such as precipitation ( P ) and temperature ( T ) dependence, may be crucial for modeling hydrological processes in impact studies. For example, the P ‐ T correlation can influence the transition between rainfall and snowfall, and also the snowmelt process (Chen et al, 2018; Meyer et al, 2019). With further development of bias correction methods, recent studies have put more effort into correcting or reconstructing the intervariable correlations of climate model outputs.…”
Section: Introductionmentioning
confidence: 99%
“…Seo et al (2019) investigated the impacts of biased P ‐ T correlation on hydrological variables over two watersheds and found that the impacts of P ‐ T correlation are more evident on low flow and subsurface hydrological variables while less remarkable to flow variables with high variability. More recently, Meyer et al (2019) compared univariate quantile mapping and MBCn in simulating hydrological variables over two alpine catchments. They found that the snow water equivalents, glacier volumes, and streamflow regime simulated using MBCn‐corrected data are consistently better than those simulated using univariate quantile mapping corrected data.…”
Section: Introductionmentioning
confidence: 99%